The Effectiveness of Authentic Assessment Instrument Based on Higher Order Thinking Skills Integrated with Character Education - Ayuningrum, Nita Dwi; Ngazizah, Nur; Ratnaningsih, Arum (Papanda Publisher, 2024)
This research aims to examine the effectiveness of the authentic assessment instrument based on Higher Order Thinking Skills (HOTS) integrated with character education on the theme